PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER SISWA KELAS V SD NEGERI 12 MEUREUDU - A’zizah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to explore the role of Islamic Religious Education teachers in instilling character values in fifth-grade students at SD Negeri 12 Meureudu. The focus of the research is to observe how values such as discipline, responsibility, hard work, and creativity are instilled in students through a conducive learning process and effective teaching methods. The research employs a qualitative field research method with a descriptive approach. Data were collected through observations, interviews, and documentation. Primary data sources came from teachers and students, while secondary data were obtained from school-related documents. Data analysis was conducted interactively using triangulation methods to ensure data validity. The results of the study indicate that Islamic Religious Education teachers play an important role as role models and facilitators in instilling character values. Supporting factors such as facilities and storytelling media facilitate the instillation of values, while challenges encountered include parents' busy schedules and environmental influences. Solutions needed include assigning tasks that increase student responsibility and cooperation between teachers and parents. This research provides in-depth insights into character-building strategies in schools and the challenges faced.